PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING TERHADAP PENINGKATAN KEMAMPUAN PENALARAN MATEMATIKA SISWA - Atik Apriati; Irfan Habibi; Abdul Rosyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Application of Problem Posing Learning Design of Mathematics Reasoning Ability Improved Student. This research was motivated by an effort to improve students' mathematical reasoning using problem posing learning design. The results obtained through experimental method pretest control group with an average value of 11.23 and the average value of the experimental group was 13.05. While the posttest results obtained by the average value of the control groupwith an average value of 18.89 and the average value of the experimental group was 13.05. From the analysis of the pretest and posttest samples can be concluded that the mathematical reasoning ability students use problem posing learning design better than mathematical reasoning abilities of students who use conventional learning design. As for the increase in mathematical reasoning ability students experimental group gained an average value is 0.48 with mathematical reasoning ability improvement criteria being and the control group gained an average value is 0.18 with the criteria of low math reasoning ability improvement. So that the analysis results can be concluded that the increase in mathematical reasoning ability students use problem posing learning design is better than the increase in mathematical reasoning abilities of students who use conventional learning. In addition, from the results of student questionnaire responses, it is known that the students showed a good response and positive impact on the problem posing learning design